Development of chromosomal markers based on next-generation sequencing: The B chromosome of the cichlid fish Astatotilapia latifasciata as a model - Fantinatti, Bruno E.A. [UNESP]; Martins, Cesar [UNESP] (Springer Nature, 2016)
Background: B chromosomes (Bs) are additional chromosomal elements found in a wide range of eukaryotes including fungi, plants and animals. B chromosomes are still enigmatic despite being the subject of hundreds, even thousands of reports. As yet there is no comprehensive theory for the biological role of B chromsomes thus, new studies are needed. Next-generation sequencing (NGS) holds promise for investigating classical issues in chromosome biology. NGS uses a large-scale approach that is required for advancing classical cytogenetic studies. Based on 454 sequencing data of a microdissected B chromosome and Illumina whole-genome sequencing data generated for 0B, 1B and 2B animals, we developed PCR- and qPCR-based markers for the B chromosomes of the cichlid fish Astatotilapia latifasciata (that possess 0, 1 or 2 B chromosomes). Results: Specific PCR primers were designed to produce two amplified fragments for B-positive samples and the control fragment for B-negative samples. Thus, PCR markers detected the presence/absence of Bs but did not provide information about the number of Bs. However, quantitative PCR (qPCR) markers clearly discriminated between 1B and 2B samples. The high copy number of the marker identified in the B chromosomes was confirmed by chromosome mapping. Conclusions: The analysis of chromosome polymorphisms based on a NGS approach is a powerful strategy to obtain markers that detect the presence/absence of extra chromosomes or the gain or loss of genomic blocks. Further, qPCR can also provide information regarding the relative copy number of specific DNA fragments. These methods are useful to investigate various chromosome polymorphisms, including B and sex chromosomes, as well as chromosomal duplications and deletions. NGS data provide a detailed analysis of the composition of genomic regions that are thought to be present in B chromosomes.
Keywords: Chromosome polymorphism; Evolution; Molecular markers; Supernumerary chromosome